An intelligent EPROM silicon compiler - Amin, A. (1991)
The authors describe an intelligent EPROM silicon compiler. The compiler accepts high-level specifications of the required EPROM design together with technology and process information and produces CMOS mask geometries for all layers. A knowledge-based kernel determines the chip architecture and required circuit blocks and calls appropriate module generators for each block. Routing algorithms are then used to connect these blocks into a full chip